Development of PjBL-Based Pancasila Education E- Module with AI-Powered Interactive Content for Strengthening Character Values High School Students in Padang City - Wulandari, Tiara; Rafni, Al; Montessori, Maria; Indrawadi, Junaidi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research aims to develop e-modules of Pancasila Education based on Project- Based Learning (PjBL) with the help of AI-Powered Interactive Content to support the strengthening of the character of high school students. The development process follows the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. The analysis stage was conducted through teacher interviews, student questionnaires, as well as curriculum and literature studies to identify the need for relevant teaching materials, student characteristics, and materials that support character value learning. The product was developed in the form of a flipbook-based interactive digital e-module that contains materials, collaborative project activities, QR-code learning videos, and character reflection elements. Validation was conducted by material, media, and language experts, with the results showing a very high level of validity in the aspects of content, language, and visual design. The practicality test involved three teachers and thirty students, resulting in an average score of 3.810 and 3.646 which indicated that the e-module was classified as very practical to use. The effectiveness test through pretest and posttest in the experimental class showed a significant increase in learning outcomes (p < .001), with Cohen's d of 3.393. In addition to cognitive improvement, character values such as caring, responsibility, and cooperation were also strengthened based on teacher assessment and student self-assessment. Based on these findings, the e-module is declared valid, practical, and effective as an alternative learning media that is contextual and relevant to the needs of the digital generation